Comparing Credit Procyclicality in Conventional and Islamic Rural Bank: Evidence from Indonesia - Arif Widodo; Mahrus Lutfi Adi Kurniawan (Al-Tijary, 2017)
Financial instability has been caused by many factors, one of which is the pro-cyclicality of credit expansion. Many empirical studies in developed countries proved that excessive credit during economic booms would be accompanied by financial crisis. In the Indonesian context, Islamic and Conventional rural bank have an important role in the provision of loans since Small Medium Enterprises still dominates economic activity.  This study aims to examine the pro-cyclicality of the credit channeled into Small Medium Enterprises by both conventional and Islamic rural banks in Indonesia; by comparing of both of which are categorized as pro-cyclicality. This study applies both Autoregressive Distributed Lag (ARDL) model to explore the extent to which the pro-cyclicality derived from indicator variables of rural banks may affect the real sector, and frequency-based filter to construct credit/financing cycle characterised by rapid growth in credit from both conventional and Islamic rural banks. The results of this study demonstrate that in the short term, conventional and Islamic rural credit banks do not follow economic growth. This means, both conventional and Islamic procyclicality do not behave in the short term. However, in the long term when the economy is in the expansion phase, Conventional rural bank tends to be more procyclical than Islamic rural banks. From the capital side, Islamic rural banks compared to Conventional bank show countercyclical behavior both in the short and long term. Moreover, to the credit risk of their bad loans, conventional rural banks have a negative response to the increase in credit risk, while Islamic rural banks are positively affected by credit risk. Finally, the results of frequency-based filter suggest that credit of conventional rural banks and financing in Islamic rural banks have different cycles in response to changing economic conditions.